Moving the Boundaries of Feminist Social Work Education with Disabled People in the Neoliberal Era. - Soldatic, Karen; Meekosha, H. (Routledge, 2012)
Until recently social work education in Australia has either marginalised or neglected disability by omission. Given the increasing number of disabled people in the community, the teaching of social work within a disability studies emancipatory paradigm as an essential part of the curriculum is long overdue. As many social work educators have suggested, we are at a critical moment in Australia, where the policy environment in which social work is embedded has largely been reframed in line with neoliberal trends. For disabled people, this has meant an ongoing state campaign to diminish disability entitlements, from decreasing disability social security regimes through to the rationalisation of adult disability support and care schemes. Social workers are negotiating the competing demands of these policy constraints alongside the needs of the disabled people they work with. New moral dilemmas have emerged where they are actively faced with the question of ‘who to serve?’.